Dinuclear Gold(I) Complexes Bearing N, N′‐Allyl‐Bridged Bisimidazolylidene Ligands. Issue 12 (28th May 2020) - Jakob, Christian H. G.; Dominelli, Bruno; Rieb, Julia; Jandl, Christian; Pöthig, Alexander; Reich, Robert M.; Correia, João D. G.; Kühn, Fritz E.
Abstract: A novel N, N'‐allyl‐bridged bisimidazolium salt and a novel dinuclear Ag(I) and a Au(I) NHC complex are reported. Both metallacyclic complexes have a twisted structural shape due to the rigid allylic system and form two different isomers relating to the position of the double bonds. The allyl‐group shows photoisomerisation, but no reactivity towards bases for the additional coordination of Pd(II). Abstract : Building bridges : A novel N, N'‐allyl‐bridged bisimidazolium salt and a novel dinuclear Ag(I) and a Au(I) NHC complex are reported. Both metallacyclic complexes have a twisted structural shape due to the rigid allylic system and form two different isomers relating to the position of the double bonds. The allyl‐group shows photoisomerisation, but no reactivity towards bases for the additional coordination of Pd(II).